EVALUATION OF TENCKHOFF CATHETER INSERTION USING OPEN SURGERY IN CHRONIC RENAL FAILURE PATIENTS - Nugroho, Indra Bayu; Singodimedjo, Prawito; Indrawarman, Indrawarman (Indonesian Urological Association, 2016)
Objective: To evaluate the dysfunction rate of Tenckhoff catheter insertion for end stage renal disease patients at Sardjito General Hospital Yogyakarta. Material & method: Data were collected from medical record retrospectively for all chronic kidney disease (CKD) patients underwent continuous ambulatory peritoneal dialysis (CAPD), by open surgery at Sardjito General Hospital Yogyakarta, from January 2010 until Desember 2013. The cause of CKD and dysfunction rate was studied. Data was analyzed using SPSS ver 18.0 (IBM corp, USA). Results: There were 43 CKD patients underwent Tenckhoff cateter placement using open surgery. Tenckhoff catheter dysfunction was found in 11.7% patients. Disfunction was caused by blockage of the catheter by omentum (6.9%) and catheter migration (4.8%). Peritonitis complication was found in 2.3% patients. The cause of CKD at Sardjito General Hospital Yogyakarta was diabetes mellitus (53.5%), hypertension (44.2%), and glomerulonefritis (2.3%). There were no correlation of dysfunction rate with gender and the cause of CKD. Conclusion: Tenckhoff catheter placement by open surgery at Sardjito General Hospital Yogyakarta have good outcome.